2018
DOI: 10.1105/tpc.17.00805
|View full text |Cite
|
Sign up to set email alerts
|

Network-Guided Discovery of Extensive Epistasis between Transcription Factors Involved in Aliphatic Glucosinolate Biosynthesis

Abstract: Plants use diverse mechanisms influenced by vast regulatory networks of indefinite scale to adapt to their environment. These regulatory networks have an unknown potential for epistasis between genes within and across networks. To test for epistasis within an adaptive trait genetic network, we generated and tested 47 double mutant combinations for 20 transcription factors, which all influence the accumulation of aliphatic glucosinolates, the defense metabolites that control fitness. The epistatic combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 103 publications
2
40
0
Order By: Relevance
“…The 20 selected TFs for this study were originally identified as binding aliphatic GLS related promoters and their knockout mutants influence aliphatic GLS accumulation (29, 30). To measure growth variation in this mutant collection, we utilized digital image analysis to measure plant size in two chambers, CEF clean chamber and LSA herbivore chamber (30). Growth was measured every other day from 9 days post-germination to 27 days at which time the leaves were overlapping.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 20 selected TFs for this study were originally identified as binding aliphatic GLS related promoters and their knockout mutants influence aliphatic GLS accumulation (29, 30). To measure growth variation in this mutant collection, we utilized digital image analysis to measure plant size in two chambers, CEF clean chamber and LSA herbivore chamber (30). Growth was measured every other day from 9 days post-germination to 27 days at which time the leaves were overlapping.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with the coordination model, a large scale yeast one hybrid study identified numerous TFs influencing both GLS accumulation and development (29). Critically, these TFs showed a large number of epistatic interactions in influencing the accumulation of GLS (30). However, previous studies did not inform on whether these TFs linked to aliphatic GLS have individual or epistatic effects on growth or flowering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic and quantitative nature of GLS biosynthesis makes it an attractive system for understanding complex transcriptional regulation, especially given that the genes and enzymes involved are almost entirely characterized (Halkier & Gershenzon 2006). Li et al (2018) have taken on this challenge, focusing on epistatic (non-additive) interactions of transcriptional regulators in aliphatic GLS biosynthesis. They generated 47 double mutants of T-DNA insertion lines for 20 TFs that regulate this process.…”
mentioning
confidence: 99%
“…Across these categories, in two tissues and two environments, Li et al (2018) find widespread and largely antagonistic epistasis in the regulatory network of aliphatic GLS biosynthesis on GLS accumulation phenotypes (e.g. Figure, which shows epistasis in short chain GLS accumulation).…”
mentioning
confidence: 99%